2012
DOI: 10.1002/adma.201203229
|View full text |Cite
|
Sign up to set email alerts
|

New Horizons for Diagnostics and Therapeutic Applications of Graphene and Graphene Oxide

Abstract: Graphene, a one-atom-thick two-dimensional (2D) layer of sp(2) -bonded carbon, has received worldwide attention owing to its extraordinary physical and chemical properties. Recently, great efforts have been devoted to explore potential applications of graphene and its oxide in life science, especially in disease-related diagnostics, near-Infrared (NIR) phototherapy and imaging. Here we will introduce recent advances and new horizons in this area, and focus on the rising progress on NIR photothermal therapy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
366
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(379 citation statements)
references
References 206 publications
(185 reference statements)
0
366
0
1
Order By: Relevance
“…Similar to carbon nanotubes and graphene [68][69][70][71][72], MCNs show strong optical absorption in the NIR region (e.g., 808 nm), indicating potential utility as the photothermal agent for photothermal ablation of cancer cells because NIR light penetrates deeply into tissues and is harmless to normal tissues [52,53]. Xu et al [53] recently demonstrated that FA-targeted MCNs showed superior photothermal-conversion efficiency compared to graphene oxide and showed that NIR irradiation accelerated the release of pre-loaded anticancer drugs from MCNs.…”
Section: Mcbs For Photothermal and Synergistic Therapymentioning
confidence: 99%
“…Similar to carbon nanotubes and graphene [68][69][70][71][72], MCNs show strong optical absorption in the NIR region (e.g., 808 nm), indicating potential utility as the photothermal agent for photothermal ablation of cancer cells because NIR light penetrates deeply into tissues and is harmless to normal tissues [52,53]. Xu et al [53] recently demonstrated that FA-targeted MCNs showed superior photothermal-conversion efficiency compared to graphene oxide and showed that NIR irradiation accelerated the release of pre-loaded anticancer drugs from MCNs.…”
Section: Mcbs For Photothermal and Synergistic Therapymentioning
confidence: 99%
“…Once their basic properties have been identified, the next main concern is their potential application. They are potential candidates for promising applications in various areas ranging from novel structural materials and field emission devices, to pharmaceutical drugdelivery vectors and also bio-sensing [1][2][3][4][5]. All these applications require some form of surface modification, which explains the great effort that has recently been devoted to such investigations [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, great efforts for multidisciplinary research have been focused on biomedical applications of 2D nanomaterials, a newly emerging subtype of nanomaterials with ultrathin layer‐structured topology, including mostly explored graphene and its derivatives,12, 13 hexagonal boron nitrides (h‐BN),14 transition metal dichalcogenides (TMDCs),15 transition metal oxides (TMOs),16 palladium (Pd) nanosheets,17 black phosphorus (BP),18, 19 and transition metal carbides (MXenes) 20. Their multifaceted properties, such as high specific surface area and intriguing physiochemical natures, make them able to satisfy the strict demands in theranostic nanomedicine such as drug delivery, phototherapy, diagnostic imaging, biosensing, and even tissue engineering 21, 22, 23, 24, 25, 26, 27, 28, 29…”
Section: Introductionmentioning
confidence: 99%